Scalable merger of chord-rings. (11th May 2010) - Kis, Zoltan Lajos; Szabo, Robert
In our previous work, we investigated how distributed hash tables – specifically chord-rings – can be merged in an efficient manner, thereby, supporting compositions of dynamic networks relying on DHTs as management substrates. As a result, we presented the chord-zip algorithm. In this paper, we present our investigations and findings on how the chord-zip algorithm can be parallelised in order to achieve scalability in the merger of chord-rings.